PEMANTAUAN KUALITAS AIR DANAU SEMAYANG DAN DANAU MELINTANG DI KABUPATEN KUTAI KARTANEGARA MENGGUNAKAN SISTEM ONLINE MONITORING - Wahjono, Heru Dwi (Jurnal Air Indonesia, 2015)
Semayang Lake and Melintang Lake in Kutai Kartanegara district, East Kalimantan is one of the biggest lake in Indonesia. Both lakes are located in the Mahakam River Basin and has an important role for economic and ecological activities in the Province of East Kalimantan. In addition to being a source of livelihood for fishermen around the lake, is also as habitat for freshwater mammals Pesut Mahakam that are endangered. Illegal logging in the forest around the lake, causing floods when it rains and water pollution will increase with sediment flowing into the lake. In some areas also get the impact of transportation activities of coal mining industry around the Mahakam River. All this causes silting almost the entire surface of the lake, lead to a reduction of existing fishery potential and cause extinction of Pesut Mahakam. To control pollution in the lake, local government of Kutai Kartanegara has implemented an online monitoring technology to monitor the water quality of the lake in four point location. Monitoring results are used to support local goverment in taking pollution control policies in both lakes. Keywords: Water quality online monitoring system, lake water quality monitoring system, GSM and SMS technology, multiprobe sensor, telemtry system.